General solution of Bernoulli and Riccati fractional differential equations based on conformable fractional derivative - Ilie, Mousa; Biazar, Jafar; Ayati, Zainab (International Journal of Applied Mathematical Research, 2017)
This paper aimed to develop two well-known nonlinear ordinary different equations, Bernoulli and Riccati equations to fractional form. General solution to fractional differential equations are detected, based on conformable fractional derivative. For each equation, numerical examples are presented to illustrate the proposed approach.